Empowering Sustainable Ecotourism Governance: Strengthening Community-Based Initiatives in Bukit Lawang - Nova Bernedeta Sitorus; Liyushiana; Muhammad Khadry; Dewi Yanti; Ngatemin (Fakultas Olahraga dan Kesehatan, Universitas PGRI Banyuwangi, 2025)
This activity aims to develop and disseminate knowledge and technology that supports sustainable ecotourism management. By referring to the Global Code of Ethics for Tourism, this PKM initiative seeks to minimize negative impacts on the environment and culture, while ensuring sustainable economic benefits for local communities. Pre-test and post-test methods were used to evaluate the effectiveness of training in increasing understanding and application of sustainable ecotourism principles among local residents. The evaluation results show significant improvements in various aspects of ecotourism management, including community involvement, environmental conservation, economic benefits, environmental education and awareness, tourism product development, tourist satisfaction, resource management, leadership and management, as well as the application of innovation and technology. This training not only increases understanding and practice related to ecotourism, but also strengthens the role of communities as agents of change. By improving local skills and knowledge, this PKM activity aims to create a better, more sustainable and globally competitive tourism ecosystem, while protecting the local environment and culture. The success of this program emphasizes the importance of community service in supporting sustainable tourism development and poverty alleviation at the village level.